Diagnostic utility of metabolic exercise testing in a patient with cardiovascular disease. Issue 4 (1st April 1999) - Elliott, P M; Hanna, M G; Ward, S A; Chinnery, P F; Turnbull, D M; Wood, N W; McKenna, W J
Abstract : Disproportionate exercise limitation in patients with cardiovascular disease is a common problem faced by clinical cardiologists and other physicians. Symptoms may be attributed to psychological factors or hypothetical pathophysiological mechanisms that are difficult to confirm clinically. This case report describes how the use of metabolic exercise testing in a 28 year old woman with morphologically and haemodynamically mild hypertrophic cardiomyopathy and severe exercise limitation led to the diagnosis of an alternative cause for the patient's symptoms, namely a primary disturbance of the mitochondrial respiratory chain probably caused by a nuclear encoded gene defect.